Pentingnya Kompetensi Komunikasi SDM Pendidikan dalam Mendukung Strategi Pemasaran Institusi - Novarita; Nurlaili; Widyatmike Gede Mulawarman (Manajemen Pendidikan Program Doktor, 2025)
Global competition among educational institutions demands marketing strategies that rely not only on formal promotional efforts but also on the communication competence of human resources (HR). Lecturers, administrative staff, and public relations personnel play a pivotal role as the frontliners in conveying the institution’s values, both directly and through digital media. This study employs a qualitative approach with a case study design at a private university in East Kalimantan. Data were collected through in-depth interviews, observation of promotional activities, and documentation of institutional communication content. The analysis was conducted through data reduction, thematic categorization, and source triangulation. Three main aspects were identified as significant contributions of communication competence to institutional marketing strategies: (1) Effective interpersonal communication (85%) contributes to strengthening student loyalty and attracting prospective students; (2) Adaptive digital communication (78%) expands information outreach and enhances the institution’s reputation through social media, email marketing, and promotional videos; (3) Internal branding through communicative services (73%) shapes a positive public perception of the institution’s quality and work culture. Communication competence of educational HR plays a strategic role in shaping the institution’s image and competitiveness. Therefore, developing interpersonal and digital communication soft skills must be integrated into educational HR management policies in a sustainable manner.